Improving Accounting for Long-Term Assets in Accordance with International Standards - Khakimov Fakhritdin Abdusattorovich (Zien Journals, 2023)
In this article, the approaches of foreign and domestic scientists to the accounting of long-term assets based on international standards, as well as the principles of recognition, evaluation and accounting of long-term assets in international standards were studied
Keywords: long-term assets; method of calculation; continuity of activit